2013
DOI: 10.4082/kjfm.2013.34.6.403
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cardiovascular Health Metrics among Korean Adults

Abstract: BackgroundAmerican Heart Association (AHA) defined 7 cardiovascular health metrics for the general population to improve cardiovascular health in 2010: not smoking; having normal blood pressure; being physically active; normal body mass index, blood glucose, and total cholesterol levels; and eating a healthy diet. To investigate trends in cardiovascular health metrics in Korea, we used data from the third and fourth Korean National Health and Nutrition Examination Surveys.MethodsWe defined seven cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 17 publications
4
26
1
Order By: Relevance
“…More specifically, in a study by Lee et al, it was reported that fewer Korean participants followed a healthy diet and had ideal glucose and cholesterol levels during the 5-year study period (2005)(2006)(2007)(2008)(2009)(2010), while more participants had ideal physical activity and blood pressure levels. 6 Furthermore, the proportion of smokers and those with ideal body mass index remained the same. This study used a limited follow-up period, mentioning that a long-term study is needed to confirm these findings.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…More specifically, in a study by Lee et al, it was reported that fewer Korean participants followed a healthy diet and had ideal glucose and cholesterol levels during the 5-year study period (2005)(2006)(2007)(2008)(2009)(2010), while more participants had ideal physical activity and blood pressure levels. 6 Furthermore, the proportion of smokers and those with ideal body mass index remained the same. This study used a limited follow-up period, mentioning that a long-term study is needed to confirm these findings.…”
mentioning
confidence: 90%
“…Investigators have also assessed the short‐term trends in the individual components defining the CVH, but data on the temporal trends in the ideal CVH over longer periods of follow‐up are limited. More specifically, in a study by Lee et al, it was reported that fewer Korean participants followed a healthy diet and had ideal glucose and cholesterol levels during the 5‐year study period (2005–2010), while more participants had ideal physical activity and blood pressure levels . Furthermore, the proportion of smokers and those with ideal body mass index remained the same.…”
mentioning
confidence: 98%
“…Prevalence of cardiovascular health, as measured with CVHI, has been examined in various populations globally and within the United States in both adults and adolescents . “Ideal” CVHI is associated with decreased CVD and decreased risk of death .…”
Section: Introductionmentioning
confidence: 99%
“…These metrics are actively used in many studies from USA and other countries [26][27][28][29]. AHA health metrics can be used for the assessment of trends in health status for primary preventive care [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…These metrics are actively used in many studies from USA and other countries [26][27][28][29]. AHA health metrics can be used for the assessment of trends in health status for primary preventive care [27,28]. Some studies showed that the number of AHA health metrics is negatively associated with stroke [30], myocardial infarction [30], cancer incidence [31] and mortality rates from all causes and CVD [27,29].…”
Section: Discussionmentioning
confidence: 99%